IMPROVEMENT OF STRUCTURE AND MECHANICAL CHARACTERISTICS OF BEARING STRUCTURES OF MOBILE MACHINES BY MEANS OF INDUCTION HEAT TREATMENT - A. I. Mihljuk; I. I. Vegera; O. A. Vegera (Литьë и металлургия)
It is shown that high-speed heating of profiled electricwelded pipes made of a steel 20PS allows to optimize mechanical characteristics and to raise constructional durability of bearing structures of automobile equipment.